Olivine-structure positive electrode material, preparation method thereof, positive electrode sheet, battery, and electric device

CN122889724APending Publication Date: 2026-10-09BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161485.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,随着终端应用对电池能量密度需求的不断提升,现有的磷酸铁锂正极材料(压实密度约为2.5g/cm3)已难以满足新能源汽车续航里程突破600km及储能系统能效优化的要求,因此,优化磷酸铁锂的压实密度(压实密度高于2.6g/cm3)成为行业研发目标

Benefits of technology

1、采用两段式微波烧结替代传统的电阻烧结,微波加热具有体积加热、升温均匀、效率高的优势,可减少晶粒长大不均匀的现象,有助于精准调控晶胞参数及颗粒粒径分布,进而稳定Rp50的分布,同时降低烧结能耗30%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889724A_ABST
    Figure CN122889724A_ABST
Patent Text Reader

Abstract

This application relates to the field of battery technology, and discloses an olivine-structured cathode material and its preparation method, cathode sheet, battery, and power device. The olivine-structured cathode material includes lithium iron phosphate cathode material particles, which comprise a carbon coating layer and a core. The core has the chemical formula Li. a Fe b M c (PO4) d M is selected from at least one of Mn, V, Co, Sr, Ni, La, Ta, Al, Cr, Zr, Ti, Mg, Ca, Nb, Sn, Sb, Mo, Si, and Na, where 0.99≤a≤1.09, 0.7≤b≤1, 0≤c≤0.3, and 0.9≤d≤1.09. The relative surface area increment coefficient F of the lithium iron phosphate cathode material satisfies: 0.6≤F≤1.8, where F=(SB-Sc) / Sc, and Sc represents the theoretical specific surface area of ​​the olivine structure cathode material in m². 2 / g, SB represents the actual measured specific surface area of ​​the olivine-structured cathode material, in m². 2 / g. This olivine-structured cathode material exhibits excellent properties such as high compaction, high rate capability, and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to an olivine-structured cathode material and its preparation method, cathode sheet, battery, and electrical device. Background Technology

[0002] Currently, lithium iron phosphate (LFP) cathode materials are gaining increasing global market share due to their high safety, long cycle life, and low cost. However, with the ever-increasing demands for battery energy density from end-use applications, existing LFP cathode materials (with a compaction density of approximately 2.5 g / cm³) are becoming increasingly less competitive. 3 The current technology is no longer sufficient to meet the requirements of increasing the driving range of new energy vehicles to over 600km and optimizing the energy efficiency of energy storage systems. Therefore, optimizing the compaction density of lithium iron phosphate (compaction density higher than 2.6g / cm³) is crucial. 3 This has become an industry research and development goal.

[0003] To achieve the above objectives, most related technologies employ targeted particle size distribution technology, which optimizes packing efficiency by mixing particles of different sizes (such as a bimodal distribution of 1μm and 5μm). This method can achieve a compaction density of 2.75 g / cm³ for lithium iron phosphate. 3 However, the aforementioned bimodal gradation will have a certain impact on electrochemical performance (e.g., larger particles will prolong the diffusion path of lithium ions, while smaller particles will have an excessively large specific surface area and more side reactions). Therefore, the research on particle gradation in the current technology is still insufficient. How to achieve better particle gradation while ensuring the electrochemical performance of lithium iron phosphate materials has become one of the current challenges. Summary of the Invention

[0004] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention proposes an olivine-structured cathode material and its preparation method, cathode sheet, battery, and power device. This olivine-structured cathode material can further optimize the particle size distribution while ensuring or even improving electrochemical performance, achieving high compaction, high rate capability, and long cycle life of the cathode material.

[0005] In a first aspect of this application, an olivine-structured cathode material is proposed, comprising lithium iron phosphate cathode material particles, wherein the lithium iron phosphate cathode material particles comprise a carbon coating layer and a core, the core having the chemical formula Li. a Fe b M c (PO4) dM is selected from at least one of Mn, V, Co, Sr, Ni, La, Ta, Al, Cr, Zr, Ti, Mg, Ca, Nb, Sn, Sb, Mo, Si, and Na, where 0.99≤a≤1.09, 0.7≤b≤1, 0≤c≤0.3, and 0.9≤d≤1.09. The relative surface area increment coefficient F of the lithium iron phosphate cathode material satisfies: 0.6 ≤ F ≤ 1.8, where F = (SB - Sc) / Sc, and Sc represents the theoretical specific surface area of ​​the olivine structure cathode material in m². 2 / g, SB represents the actual measured specific surface area of ​​the olivine-structured cathode material, in m². 2 / g.

[0006] The aforementioned relative surface area increment coefficient F can be used to characterize the increase ratio of the actual tested specific surface area (i.e., the total adsorbable surface area) of the target material relative to the theoretical specific surface area (i.e., the theoretical external surface area of ​​a smooth spherical single crystal particle). For the olivine-structured cathode material in this application, since it is composed of primary particles with a carbon coating, its actual tested specific surface area includes the outer surface of the core, the surface of the carbon coating, and the micropores and mesopores within the carbon layer. For example, without a carbon coating, the core surface is smooth and non-porous, and F is approximately 0; while with the introduction of a carbon coating, F > 0. Therefore, it can be explained that: the larger the relative surface area increment coefficient F of the olivine structure cathode material, the higher the carbon content of the target material and the loose and porous carbon coating layer, which will lead to the loose powder of the target material, the lower compaction density, and ultimately the generation of gas during battery cycling, thus reducing its electrochemical performance; on the other hand, the smaller the relative surface area increment coefficient F of the olivine structure cathode material, the lower the carbon content or the dense and non-porous carbon layer, which will lead to insufficient conductive channels in the cathode material, thus increasing the internal resistance of the battery and reducing its electrochemical performance.

[0007] Therefore, this application limits the relative surface area increment coefficient F of the target olivine structure cathode material to a range of 0.6 to 1.8 to ensure that the carbon content in the target cathode material is appropriate and that there is an appropriate amount of pore structure in the carbon coating layer, which can form a uniform and continuous porous conductive network. At the same time, it can take into account the compaction density of the target particles, thereby achieving high compaction, high rate, and long cycle life of the olivine structure cathode material.

[0008] In addition, the olivine structure cathode material according to the above embodiments of this application may also have the following additional technical features: In some embodiments, the relative surface area increment coefficient F of the olivine structure cathode material satisfies: 0.7 ≤ F ≤ 1.7.

[0009] In some embodiments, the olivine-structured cathode material satisfies at least one of the following conditions: The Sc of the olivine-structured cathode material is 4.0m. 2 / g~9.0m 2 / g; The SB of the olivine-structured cathode material is 9.0m. 2 / g~15.0m 2 / g.

[0010] In some embodiments, the theoretical specific surface area of ​​the olivine-structured cathode material is Sc = 6 / (ρ × D). A ), where ρ is 3.6 g / cm³ 3 , representing the true density of the olivine-structured cathode material, D A The value represents the average particle size of the lithium iron phosphate cathode material particles, in μm.

[0011] In some embodiments, the particle size distribution curve of the olivine structure cathode material includes two characteristic peaks, wherein the peak position of the first characteristic peak is 0.3 μm to 0.7 μm and the peak position volume percentage of the first characteristic peak is Pv1, the peak position of the second characteristic peak is 1.0 μm to 2.5 μm and the peak position volume percentage of the second characteristic peak is Pv2, and the peak intensity ratio I of the volume distribution of the olivine structure cathode material satisfies: 0.7 ≤ I = Pv1 / Pv2 ≤ 1, preferably 0.75 ≤ I = Pv1 / Pv2 ≤ 0.96.

[0012] In some embodiments, the olivine-structured cathode material satisfies at least one of the following conditions: Pv1 was 4%~6%; Pv2 is 5%~7%.

[0013] In some embodiments, the olivine-structured cathode material satisfies at least one of the following conditions: The D of the olivine structure cathode material 50 The micrometer size is 0.8 μm to 2.0 μm, preferably 1.0 μm to 1.8 μm; Based on the total mass of the olivine-structured cathode material, the carbon content is 1.0 wt% to 2.0 wt%; The compaction density of the olivine-structured cathode material is 2.60 g / cm³. 3 ~2.90g / cm 3 .

[0014] A second aspect of this application provides a method for preparing the aforementioned olivine-structured cathode material, comprising: First lithium iron phosphate particle precursor and second lithium iron phosphate particle precursor were prepared respectively. The first lithium iron phosphate particle precursor is subjected to a first sintering to obtain the first lithium iron phosphate particle, and the second lithium iron phosphate particle precursor is subjected to a second sintering to obtain the second lithium iron phosphate particle. The first lithium iron phosphate particles, the second lithium iron phosphate particles, the grinding aid and the solvent are mixed, dried, pulverized and sintered in sequence to obtain an olivine structure cathode material. Among them, the R of the first lithium iron phosphate particle p50 The R of the second lithium iron phosphate particles is 0.4μm~1μm. p50 The particle size ranges from 1.43 μm to 3.33 μm. By controlling the Rp50 of the first and second lithium iron phosphate particles, the two particle sizes can be graded to obtain the target cathode material.

[0015] In some embodiments, at least one of the following conditions is met: The preparation method of the first lithium iron phosphate particle precursor includes: mixing a lithium source, an iron source, a phosphorus source, an optional dopant, a first carbon source according to a target chemical ratio and a solvent, and spray drying to obtain the first lithium iron phosphate particle precursor, wherein the first carbon source includes at least one of glucose, sucrose, PVP, oxalic acid, water-soluble phenolic resin, PAA, starch, ascorbic acid, citric acid, lignin, PEG, and PV. The preparation method of the second lithium iron phosphate particle precursor includes: mixing a lithium source, an iron source, a phosphorus source, an optional dopant, a second carbon source according to a target chemical ratio and a solvent, and spray drying to obtain the second lithium iron phosphate particle precursor. The second carbon source includes at least one of glucose, sucrose, PVP, oxalic acid, water-soluble phenolic resin, PAA, ascorbic acid, citric acid, starch, asphalt, PEG, and PVA.

[0016] In some embodiments, at least one of the following conditions is met: The iron source includes at least one of ferric carbonate, ferrous oxide, ferric oxide, iron powder, ferric oxide, ferrous oxalate, and ferric phosphate. The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxide, lithium dihydrogen phosphate, and lithium phosphate. The phosphorus source includes at least one of sodium phosphate, potassium phosphate, phosphoric acid, and monoammonium phosphate.

[0017] In some embodiments, the drying is vacuum freeze-drying, and the vacuum freeze-drying satisfies at least one of the following conditions: The temperature for vacuum freeze drying is -40℃ to -50℃; The vacuum degree of the vacuum freeze-drying is 1~5 Pa; The vacuum freeze-drying time is 8h~12h.

[0018] In some embodiments, the first sintering includes sequentially performing a first-stage sintering and a second-stage sintering, and the second sintering includes sequentially performing a third-stage sintering and a fourth-stage sintering, and satisfies at least one of the following conditions: The sintering rate of the first section is 5℃ / min~8℃ / min; The sintering temperature of the first section is 400℃~450℃; The sintering time for the first stage is 2 to 3 hours. The sintering rate of the two stages is 5℃ / min~8℃ / min; The temperature for the two-stage sintering is 750℃~830℃; The sintering time for the two stages is 6 hours to 15 hours. The sintering rate of the three sections is 5℃ / min~8℃ / min; The sintering temperature for the three stages is 350℃~400℃; The sintering time for the three stages is 1 hour to 2 hours; The sintering rate of the four sections is 5℃ / min~8℃ / min; The sintering temperature for the four sections is 680℃~780℃; The sintering time for the four sections is 4h~12h; The temperature of the third sintering is 720℃~800℃; The third sintering time is 5h~14h. This helps to obtain the target first lithium iron phosphate particles and second lithium iron phosphate particles, thereby obtaining a cathode material with excellent performance.

[0019] In some embodiments, at least one of the following conditions is met: The mass ratio of the first lithium iron phosphate particle to the second lithium iron phosphate particle is (1:5) to (2:1); Based on the total mass of the first lithium iron phosphate particles, the second lithium iron phosphate particles, and the grinding aid, the mass percentage of the grinding aid is 0.1wt%~2wt%. The grinding aid includes inorganic grinding aid and organic grinding aid, and the mass ratio of the inorganic grinding aid to the organic grinding aid is (1~5):(1~5). The dopant includes at least one of the following: oxide, hydroxide, sulfate, carbonate, phosphate, fluoride, and chloride of M; The temperature for vacuum freeze drying is -40℃ to -50℃; The vacuum degree of the vacuum freeze-drying is 1~5 Pa; The vacuum freeze-drying time is 8 to 12 hours. This helps to obtain target materials with excellent performance.

[0020] In some embodiments, at least one of the following conditions is met: The inorganic grinding aid includes at least one of metal oxides and phosphates; The organic grinding aid includes at least one of polyacrylates, alcohols, and fatty acids. This contributes to obtaining the target material with excellent performance.

[0021] A third aspect of this application provides a positive electrode sheet comprising the aforementioned olivine-structured positive electrode material, or an olivine-structured positive electrode material prepared by the aforementioned preparation method. Therefore, this positive electrode sheet exhibits excellent electrochemical performance.

[0022] A fourth aspect of this application provides a battery comprising the aforementioned positive electrode. Therefore, the battery exhibits excellent electrochemical performance.

[0023] A fifth aspect of this application provides an electrical device comprising the aforementioned battery. Therefore, this electrical device exhibits excellent electrochemical performance and a long lifespan. Attached Figure Description

[0024] Figure 1 This is a SEM image of the first lithium iron phosphate particles prepared in Example 1 of this application.

[0025] Figure 2 This is a SEM image of the second lithium iron phosphate particles prepared in Example 1 of this application.

[0026] Figure 3 This is a SEM image of the olivine-structured cathode material prepared in Example 1 of this application. Detailed Implementation

[0027] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0028] As mentioned earlier, in order to further optimize the particle size distribution technology, the inventors considered preparing two particles with different cell parameters and mixing them to achieve high compaction of the target material while also precisely controlling the relative specific surface area increment coefficient of the target material, thereby ensuring that the target material has excellent electrochemical performance.

[0029] In view of this, the first aspect of this application proposes an olivine-structured cathode material, comprising lithium iron phosphate cathode material particles, wherein the lithium iron phosphate cathode material particles comprise a carbon coating layer and a core, the core having the chemical formula Li. a Fe b M c (PO4) d M is selected from at least one of Mn, V, Co, Sr, Ni, La, Ta, Al, Cr, Zr, Ti, Mg, Ca, Nb, Sn, Sb, Mo, Si, and Na, where 0.99 ≤ a ≤ 1.09, 0.7 ≤ b ≤ 1, 0 ≤ c ≤ 0.3, and 0.9 ≤ d ≤ 1.09. The relative surface area increment coefficient F of the olivine structure cathode material satisfies: 0.6 ≤ F ≤ 1.8, where F = (SB - Sc) / Sc, and Sc represents the theoretical specific surface area of ​​the olivine structure cathode material in m². 2 / g, SB represents the actual measured specific surface area of ​​the olivine-structured lithium cathode material, in m². 2 / g.

[0030] The aforementioned relative surface area increment coefficient F can be used to characterize the increase ratio of the actual tested specific surface area (i.e., the total adsorbable surface area) of the target material relative to the theoretical specific surface area (i.e., the theoretical external surface area of ​​a smooth spherical single crystal particle). For the olivine-structured cathode material in this application, since it is composed of primary particles with a carbon coating, its actual tested specific surface area includes the outer surface of the core, the surface of the carbon coating, and the micropores and mesopores within the carbon layer. For example, without a carbon coating, the core surface is smooth and non-porous, and F is approximately 0; while with the introduction of a carbon coating, F > 0. Therefore, it can be explained that: the larger the relative surface area increment coefficient F of the olivine structure cathode material, the higher the carbon content of the target material and the loose and porous carbon coating layer, which will lead to the loose powder of the target material, the lower compaction density, and ultimately the generation of gas during battery cycling, thus reducing its electrochemical performance; on the other hand, the smaller the relative surface area increment coefficient F of the olivine structure cathode material, the lower the carbon content or the dense and non-porous carbon layer, which will lead to insufficient conductive channels in the cathode material, thus increasing the internal resistance of the battery and reducing its electrochemical performance.

[0031] Therefore, this application limits the relative surface area increment coefficient F of the target olivine structure cathode material to a range of 0.6 to 1.8 to ensure that the carbon content in the target cathode material is appropriate and that there is an appropriate amount of pore structure in the carbon coating layer, which can form a uniform and continuous porous conductive network. At the same time, it can take into account the compaction density of the target particles, thereby achieving high compaction, high rate, and long cycle life of the olivine structure cathode material.

[0032] For example, F can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, or any range between the two. This essentially ensures that the olivine-structured lithium cathode material has a high compaction density, and that the carbon coating layer can form a uniform and continuous porous conductive network, thereby improving the battery's rate performance, cycle performance, and other properties.

[0033] Furthermore, F can be 0.7 to 1.7, and for example, it can be 0.7, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, etc. This helps to further achieve the goals of high compaction, high rate capability, and high cycle life of olivine structure cathode materials.

[0034] In some embodiments, the Sc of the olivine-structured cathode material is 4.0m. 2 / g~9.0m 2 / g, specifically, it can be 4.0m 2 / g, 4.5m 2 / g, 5.0m 2 / g, 5.5m 2 / g, 6.0m 2 / g, 6.5m 2 / g, 7.0m 2 / g, 7.5m 2 / g, 8.0m 2 / g, 8.5m 2 / g, 9.0m 2 / g etc. According to the chemical formula defined for lithium iron phosphate cathode material particles in this application, the theoretical specific surface area Sc of the target olivine structure cathode material is basically within the above range.

[0035] Furthermore, the SB of the olivine-structured cathode material is 9.0m. 2 / g~15.0m 2 / g, specifically, it can be 9.0m 2 / g, 9.5m 2 / g, 10.0m 2 / g, 10.5m 2 / g, 11.0m 2 / g, 11.5m 2 / g, 12.0m 2 / g, 12.5m 2 / g, 13.0m 2 / g, 13.5m 2 / g, 14.0m 2 / g, 14.5m 2 / g, 15.0m 2 / g etc. The above range can basically ensure that the carbon content in the target cathode material is moderate and that the carbon coating layer has an appropriate amount of pore structure, which helps to form a uniform and continuous porous conductive network, ultimately improving the rate performance and cycle performance of the battery.

[0036] The theoretical specific surface area of ​​the olivine-structured cathode material mentioned above is Sc = 6 / (ρ×D). A ), where ρ represents the true density of the olivine-structured cathode material (i.e., the density of the solid framework itself in the olivine-structured cathode material, which is 3.6 g / cm³). 3 ); D A This indicates the average particle size of lithium iron phosphate cathode material particles (specifically, the average particle size of lithium iron phosphate cathode material particles can be tested using a scanning electron microscope (SEM), and the unit of the average particle size of lithium iron phosphate cathode material particles is basically 0.10μm~0.5μm).

[0037] Specifically, the particle size of lithium iron phosphate (LFP) cathode material can be detected using the following method: For olivine-structured cathode active materials, 30.0K magnification SEM images were captured using an ERA-9200 scanning electron microscope (SEM) from ELIONIX (Japan). The LIBMAS intelligent image analysis system was used to perform contrast analysis on the SEM images, determining the area of ​​any single particle (i.e., any LFP cathode material particle). A circle with the same area as a single particle is considered an equivalent circle. The average diameter of these circles is calculated, which represents the average particle size of the LFP cathode material. Ten 30K images were analyzed for each sample, resulting in the size analysis of approximately 800-1500 LFP cathode material particles, and the average size was calculated.

[0038] Furthermore, the actual test specific surface area (SB) of the olivine-structured cathode material can be tested using the following method: At liquid nitrogen temperature, an inert gas (such as nitrogen) is physically adsorbed onto the sample surface; the adsorption amount is measured at different pressures by varying the gas pressure; the adsorption data is processed according to the BET formula to calculate the monolayer saturated adsorption amount; and the specific surface area per unit weight of the sample is calculated by combining the cross-sectional area of ​​the adsorbed molecules. The above tests are performed using a surface analyzer; for example, the Tristar 3020 surface analyzer from Micromeritics can be used.

[0039] In some embodiments, the particle size distribution curve of the olivine structure cathode material is tested in accordance with the standard GB / T19077-2016 "Particle size distribution by laser diffraction method" and measured using a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0040] The curve includes two characteristic peaks. The first characteristic peak has a peak position of 0.3 μm to 0.7 μm (exemplarily, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or any range between two), and the peak position volume percentage of the first characteristic peak is Pv1. The second characteristic peak has a peak position of 1.0 μm to 2.5 μm (exemplarily, it can be 1.0 μm, 1.2 μm, 1.5 μm, 2.0 μm, 2.5 μm, or any range between two), and the peak position volume percentage of the second characteristic peak is Pv2. The volume distribution peak intensity ratio I of the olivine structure cathode material satisfies: 0.7 ≤ I = Pv1 / Pv2 ≤ 1. Therefore, it can be basically guaranteed that the gradation of particles of different sizes is achieved in the olivine structure cathode material, thereby ensuring that fine particles (i.e., smaller particles) fully fill the gaps between coarse particles, reducing the powder porosity, and thus improving the compaction density of the electrode and the energy density of the battery. On the other hand, the interconnection between coarse and fine particles forms a continuous conductive network, ensuring sufficient lithium-ion transport channels, which helps improve the rate performance and low-temperature performance of the cathode material. It also helps optimize powder flowability and slurry processing characteristics during the manufacturing process, reducing mass production issues such as material shedding during coating and electrode surface defects. Furthermore, the gradation of particles with different sizes helps to further precisely control the specific surface area of ​​the cathode material within a reasonable range, thereby helping to improve problems such as electrolyte side reactions and gas generation during cycling, and enhancing the electrochemical performance of the battery.

[0041] For example, the volume distribution peak intensity ratio I of the olivine-structured cathode material can be 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, or any range between the two. This range helps to further achieve high compaction, high rate capability, and long cycle life of the cathode material.

[0042] Furthermore, the volume distribution peak intensity ratio I of the olivine structure cathode material satisfies: 0.75 ≤ I = Pv1 / Pv2 ≤ 0.99. For example, it can be 0.75, 0.8, 0.85, 0.9, 0.96, etc. I within the above range helps to further achieve high compaction, high rate capability, and long cycle life of the cathode material.

[0043] In some embodiments, the volume percentage of the first characteristic peak, Pv1, can be 4% to 6% (exemplarily, it can be 4%, 5%, 6%, or any range between the two); the volume percentage of the second characteristic peak, Pv2, can be 5% to 7% (exemplarily, it can be 5%, 6%, 7%, or any range between the two). These ranges generally ensure that the volume distribution peak intensity ratio I is within the preferred range of 0.7 to 1, guaranteeing a matching ratio of fine to coarse particles. On the one hand, this allows fine particles to fully fill the gaps between coarse particles, reducing powder porosity and increasing electrode compaction density; on the other hand, it ensures that the specific surface area of ​​the target cathode material is moderate, and the lithium-ion solid-phase diffusion distance is moderate, thereby improving the electrochemical performance of the cathode material.

[0044] In some embodiments, the D of the olivine-structured cathode material 50 The micrometer size ranges from 0.8 μm to 2.0 μm, preferably from 1.0 μm to 1.8 μm. Specifically, it can be 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, etc. This applies to the D-type cathode material with an olivine structure. 50 Within the aforementioned range, the lithium-ion diffusion path remains within a suitable range, making the lithium-ion insertion / extraction process more efficient and improving charge / discharge kinetics performance. This essentially avoids the D-type degradation of the cathode material. 50 Excessively small particle size may lead to particle agglomeration, increasing the resistance to lithium-ion diffusion and the D of the cathode material. 50 Excessively large particle size may result in an excessively long lithium-ion diffusion path, slowing down the electrochemical reaction.

[0045] Specifically, D 50 The particle size refers to the percentage of particles smaller than 50% in the lithium iron phosphate cathode material. The above D... 50 Particle size can be tested using a Malvern particle size analyzer.

[0046] In some embodiments, the compaction density of the olivine-structured cathode material is 2.60 g / cm³. 3 ~2.90g / cm 3 Specifically, it can be 2.60 g / cm³. 3 2.65g / cm 3 2.7g / cm 3 2.75g / cm 3 2.8g / cm 3 2.85g / cm 3 2.9g / cm 3 The compaction density within the above range can basically ensure sufficient contact between the cathode material particles, thereby ensuring the electronic conductivity of the electrode, reducing the internal resistance of the electrode, promoting the electrochemical reaction, and improving the power performance of the battery.

[0047] Specifically, compaction density is a physical parameter that measures the mass of a unit volume of loose solid material (such as the cathode material particles mentioned above) after it has been compacted under external pressure. Essentially, it reflects the degree to which the voids between the material particles are compressed. The compaction density of particles can be calculated using ρ=m / v, where m is the mass of the particle (in grams) and v is the total volume of the compacted particles (in centimeters). 3 .

[0048] In some embodiments, based on the total mass of the olivine-structured cathode material, the carbon content is 1.0 wt% to 2.0 wt%, specifically, it can be 1.0 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, 2.0 wt%, etc. A carbon content within the above range can generally ensure a moderate carbon coating thickness for the lithium iron phosphate cathode material particles, generally ensure the formation of a continuous and dense interface protection on the core surface, and ensure the structural stability of the cathode material. Simultaneously, it can maximize the rate performance and energy density of the core.

[0049] The carbon content mentioned above can be tested directly using the Beijing Wanlianda CS-901B carbon and sulfur analyzer.

[0050] A second aspect of this application provides a method for preparing the aforementioned olivine-structured cathode material, comprising: S10: Prepare the first lithium iron phosphate particle precursor and the second lithium iron phosphate particle precursor, respectively.

[0051] In this step, lithium source, iron source, phosphorus source, optional dopant, and carbon source are mixed according to the target chemical ratio and solvent, and then spray-dried to obtain the particulate precursor. It should be noted that the type of carbon source used in the preparation of the first and second lithium iron phosphate particulate precursors is not limited; they can be the same or different carbon sources. For example, in the preparation of the first lithium iron phosphate particulate precursor, a highly active carbon source can be used, i.e., one that can rapidly undergo carbonization reactions and more easily form porous and continuous amorphous carbon, which helps to improve lithium-ion transport and thus improve the rate performance of the battery. However, this type of carbon source is expensive. Therefore, in this application, the first and second lithium iron phosphate particulate precursors can be prepared using a highly active carbon source and a less active carbon source (which is relatively inexpensive), respectively, which can ensure the electrochemical performance of the final cathode material while reducing costs to some extent.

[0052] For example, the preparation method of the first lithium iron phosphate particle precursor includes: mixing a lithium source (lithium carbonate), an iron source (iron phosphate), a phosphorus source (phosphoric acid), an optional dopant, a first carbon source, and a solvent according to a target chemical ratio (mixing is performed by ultrasonic dispersion combined with ball milling), and then spray drying (the inlet air temperature during spray drying is 200℃~300℃, and the outlet air temperature is 90℃~120℃) to obtain the first lithium iron phosphate particle precursor. The first carbon source includes, but is not limited to, glucose, sucrose, PVP, oxalic acid, water-soluble phenolic resin, PAA, starch, ascorbic acid, citric acid, lignin, PEG, PVA, etc. A suitable carbon source can be selected according to actual conditions.

[0053] Specifically, the ultrasonic dispersion power during mixing is 300W~500W, the ultrasonication time is 20min~40min, the ball milling speed is 300rpm~500rpm, and the ball milling time is 1h~2h. This ensures a relatively uniform first lithium iron phosphate particle precursor and maintains a relatively high Dg of the first lithium iron phosphate particle precursor. 50 It is approximately 0.25μm to 0.5μm.

[0054] Furthermore, the preparation method of the second lithium iron phosphate particle precursor includes: mixing a lithium source (lithium carbonate), an iron source (iron phosphate), a phosphorus source (phosphoric acid), an optional dopant, a second carbon source, and a solvent according to a target chemical ratio, and then spray drying to obtain the second lithium iron phosphate particle precursor. The second carbon source includes, but is not limited to, glucose, sucrose, PVP, oxalic acid, water-soluble phenolic resin, PAA, ascorbic acid, citric acid, starch, asphalt, PEG, PVA, etc. The mixing conditions are the same as described above and will not be repeated here.

[0055] In some embodiments, the iron source includes at least one selected from ferric carbonate, ferrous oxide, ferric oxide, iron powder, magnetite, ferrous oxalate, and ferric phosphate. The lithium source includes at least one selected from lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxide, lithium dihydrogen phosphate, and lithium phosphate. The phosphorus source includes at least one selected from sodium phosphate, potassium phosphate, phosphoric acid, and monoammonium phosphate.

[0056] The dopants mentioned above include at least one of the following: oxides, hydroxides, sulfates, carbonates, phosphates, fluorides, and chlorides of M. The specific type is not limited and can be selected according to the actual conditions.

[0057] The solid content of the solvent and slurry mentioned above is not limited, as long as it can fully disperse the raw materials. For example, the solvent can be at least one of water and ethanol. Preferably, the solid content of the slurry is ≥35%. For example, the solid content of the slurry can be 35%, 40%, 45%, 50%, etc.

[0058] It should be noted that the solvent used in the preparation of the first lithium iron phosphate particle precursor and the second lithium iron phosphate particle precursor is preferably an alcohol-based inert dispersing solvent. For example, ethanol can be used as the solvent in the preparation of both the first lithium iron phosphate particle precursor and the second lithium iron phosphate particle precursor.

[0059] S20: The first lithium iron phosphate particle precursor is subjected to a first sintering to obtain the first lithium iron phosphate particle, and the second lithium iron phosphate particle precursor is subjected to a second sintering to obtain the second lithium iron phosphate particle.

[0060] In this step, the first sintering includes sequential first-stage sintering and second-stage sintering, and the second sintering includes sequential third-stage sintering and fourth-stage sintering. In this application, the heating process is carried out in an inert atmosphere using microwave heating. Microwave heating has advantages such as volume heating, uniform heating, and high efficiency. It can reduce the phenomenon of uneven grain growth, help to accurately control the particle size distribution, and thus help to stabilize the Rp50 distribution of the particles, while reducing sintering energy consumption by more than 30%.

[0061] In some embodiments, the sintering rate of the first stage is 5°C / min to 8°C / min (exemplary values ​​include 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc.), the sintering temperature of the first stage is 400°C to 450°C (exemplary values ​​include 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, etc.), and the sintering time of the first stage is 2h to 3h (exemplary values ​​include 2h, 2.5h, 3h, etc.). The first stage sintering is a low-temperature pre-sintering, under which impurities and products from the decomposition of the first carbon source in the first lithium iron phosphate particle precursor can be removed. Simultaneously, a heating rate within the above range can generally ensure uniform heating of the precursor during the heating process, contributing to a uniform structure of the obtained first lithium iron phosphate particles. This largely avoids uneven heating of the precursor caused by excessively rapid heating rates, which can easily lead to localized overheating and damage to the structural stability of the product.

[0062] Furthermore, the sintering rate for the second stage is 5℃ / min to 8℃ / min (exemplary values ​​could be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, etc.), the sintering temperature is 750℃ to 830℃ (exemplary values ​​could be 750℃, 760℃, 780℃, 800℃, 820℃, 830℃, etc.), and the sintering time is 6h to 15h (exemplary values ​​could be 6h, 8h, 10h, 12h, 15h, etc.). Finally, after natural cooling to room temperature, the first lithium iron phosphate particles are obtained. The second-stage sintering is a high-temperature sintering process. Under the above conditions, the particle size distribution of the first lithium iron phosphate particles can be basically controlled, thereby improving the R... p50Within the target range. The R of the first lithium iron phosphate particles. p50 The range is 0.4μm to 1μm, with the unit being μm.

[0063] For example, the first lithium iron phosphate particle precursor is placed in a microwave sintering furnace and subjected to first-stage sintering and second-stage sintering in an inert gas atmosphere (argon and nitrogen in a volume ratio of 1:1).

[0064] The R of the first lithium iron phosphate particles mentioned above p50 =D 50 / I1, where I1 is the volume distribution peak intensity ratio of the first lithium iron phosphate particle obtained by Malvern particle size analyzer; D 50 This refers to the particle size value corresponding to the 50% position of the volume distribution obtained from the Malvern particle size analyzer. In other words, performing the first sintering under the above conditions can improve the R... p50 Within the target range. This helps optimize the packing structure of the first lithium iron phosphate particles, reduce interparticle voids, and increase compaction density. Specifically, the volume distribution curve of the first lithium iron phosphate particles also has two characteristic peaks, and the calculation method for the volume distribution peak intensity ratio is the same as described above, and will not be repeated here.

[0065] In some embodiments, the three-stage sintering rate is 5℃ / min to 8℃ / min (exemplary values ​​could be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, etc.), the three-stage sintering temperature is 350℃ to 400℃ (exemplary values ​​could be 350℃, 360℃, 370℃, 380℃, 390℃, 400℃, etc.), and the three-stage sintering time is 1h to 2h (exemplary values ​​could be 1h, 1.5h, 2h, etc.). As described above, the three-stage sintering is a low-temperature pre-sintering process, under which impurities and decomposition products of the second lithium iron phosphate particle precursor can be removed. Simultaneously, a heating rate within the above range can generally ensure uniform heating of the precursor during the heating process, contributing to a uniform structure of the obtained second lithium iron phosphate particles. This largely avoids uneven heating of the precursor caused by excessively rapid heating rates, which could easily lead to localized overheating and damage to the structural stability of the product.

[0066] Furthermore, the sintering rate for the four stages is 5℃ / min to 8℃ / min (exemplary values ​​could be 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, etc.); the sintering temperature for the four stages is 680℃ to 780℃ (exemplary values ​​could be 680℃, 700℃, 720℃, 740℃, 760℃, 780℃, etc.); and the sintering time for the four stages is 4h to 12h (exemplary values ​​could be 4h, 6h, 8h, 10h, 12h, etc.). Finally, after natural cooling to room temperature, the second lithium iron phosphate particles are obtained. The four-stage sintering is a high-temperature sintering process. Under the above conditions, the Rp50 of the second lithium iron phosphate particles can be basically controlled within the target range. p50 The range is 1.43μm to 3.33μm.

[0067] R of lithium iron phosphate particles p50 =D 50 / I2, where I2 is the volume distribution peak intensity ratio of the second lithium iron phosphate particles obtained by Malvern particle size analyzer; D 50 This represents the particle size value corresponding to the 50% position of the second lithium iron phosphate particle volume distribution obtained by the Malvern particle size analyzer.

[0068] In summary, the Rp values ​​of the first and second lithium iron phosphate particles obtained through the first and second sintering processes are... 50 Within the above range, it can be basically guaranteed that the specific surface area of ​​the lithium iron phosphate cathode material particles (i.e., the target cathode material) obtained by mixing the two types of particles is within the target range, thereby ensuring that the target material achieves high compaction, high rate, and long cycle life.

[0069] S30: The first lithium iron phosphate particles, the second lithium iron phosphate particles, the grinding aid and the solvent are mixed, dried, pulverized and sintered in sequence to obtain an olivine structure cathode material. In this step, the first lithium iron phosphate particles, the second lithium iron phosphate particles, and the grinding aid obtained above are dispersed in a solvent and then dried and pulverized in sequence to obtain the target cathode material.

[0070] For example, the mixing process can be carried out by ultrasonic dispersion, which helps to ensure that the first lithium iron phosphate particles and the second lithium iron phosphate particles are evenly dispersed in the solvent. The ultrasonic power is 400W~600W and the ultrasonic time is 30min~60min.

[0071] Furthermore, the drying process can be vacuum freeze-drying, with a temperature of -40℃ to -50℃ (exemplary values ​​include -50℃, -48℃, -46℃, -44℃, -42℃, -40℃, etc.), a vacuum degree of 1 to 5 Pa (exemplary values ​​include 1 Pa, 2 Pa, 3 Pa, 4 Pa, 5 Pa, etc.), and a freeze-drying time of 8 hours to 12 hours (exemplary values ​​include 8 hours, 10 hours, 12 hours, etc.). This application uses vacuum freeze-drying instead of conventional drying, which largely avoids particle agglomeration during the drying process, ensuring uniform mixing of the two types of particles, ultimately improving the consistency of the overall performance of the cathode material and better meeting the precision requirements of large-scale industrial production.

[0072] In some embodiments, the temperature of the third sintering is 720℃~800℃, specifically, it can be 720℃, 750℃, 780℃, 800℃, etc. Furthermore, the time of the third sintering is 5h~14h, specifically, it can be 5h, 8h, 10h, 12h, 14h, etc. Therefore, it is basically possible to obtain a target cathode material with stable structure and a specific surface area within the target range.

[0073] In some embodiments, the mass ratio of the first lithium iron phosphate particle to the second lithium iron phosphate particle is (2:1) to (1:5), specifically, it can be 2:1, 2:5, 1:1, 1:5, etc. Specifically, the Rp of the first lithium iron phosphate particle and the second lithium iron phosphate particle... 50 All are within the specified range. On this basis, further limiting the mixing mass ratio of the two particles helps to accurately control the overall specific surface area of ​​the lithium iron phosphate cathode material particles after mixing, which can basically ensure that the relative surface area increment coefficient of the lithium iron phosphate cathode material particles is within the target range. At the same time, it also helps to achieve the optimal gradation and packing of the two particles, reduce the powder porosity, and improve the compaction density of the cathode material.

[0074] In some embodiments, based on the total mass of the first lithium iron phosphate particles, the second lithium iron phosphate particles, and the grinding aid, the mass percentage of the grinding aid is 0.1wt% to 2wt%, specifically, it can be 0.1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, etc. A mass percentage of grinding aid within the above range can fully exert its function of dispersing and breaking up particle agglomeration, ensuring uniform mixing of the two types of particles, and ultimately obtaining a cathode material with excellent electrochemical performance.

[0075] Furthermore, the grinding aid includes inorganic and organic grinding aids, and the mass ratio of the inorganic to the organic grinding aid is (1~5):(1~5), specifically, it can be 1:1, 2:2, 1:3, 1:5, 3:2, 5:1, etc. The organic grinding aid can achieve stable dispersion of particles in the liquid phase through electrostatics and steric hindrance, while the inorganic grinding aid acts as a micro-grinding medium, assisting in breaking up particle agglomerations. Therefore, within the above-mentioned mass ratio range, the two types of particles can be thoroughly mixed, which is beneficial for obtaining secondary particles with controllable particle size distribution and specific surface area, ultimately ensuring that the cathode material possesses excellent compaction density, rate performance, and cycle stability.

[0076] For example, inorganic grinding aids include at least one of metal oxides and phosphates, wherein the metal oxides include, but are not limited to, silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, etc. Organic grinding aids include at least one of polyacrylates, alcohols, and fatty acids.

[0077] The method for preparing lithium iron phosphate cathode material in this application has at least the following beneficial effects: 1. Two-stage microwave sintering is used to replace traditional resistance sintering. Microwave heating has the advantages of volumetric heating, uniform temperature rise, and high efficiency. It can reduce the phenomenon of uneven grain growth, which helps to accurately control the cell parameters and particle size distribution, thereby stabilizing R. p50 The distribution of energy is improved, while reducing sintering energy consumption by more than 30%.

[0078] 2. Different precursors were prepared (using different carbon sources and different dispersion systems) to adapt to the particle characteristics of the two types of lithium iron phosphate, avoiding problems such as small particle agglomeration or structural defects in large particles.

[0079] 3. Ultrasonic-assisted dispersion is carried out throughout the entire process of precursor preparation and mixing, which can further improve particle dispersibility, optimize particle packing efficiency, enhance the uniformity of carbon coating, reduce carbon coating defects, and help to synergistically improve the conductivity and structural stability of the material.

[0080] 4. Vacuum freeze drying replaces conventional drying, which can improve the particle agglomeration phenomenon during conventional drying, ensure further uniform mixing of the two types of lithium iron phosphate particles, and guarantee R... p50 The stability of parameters ultimately improves the consistency of the overall performance of materials, making them more suitable for the precision requirements of large-scale industrial production.

[0081] A third aspect of this application provides a positive electrode sheet, specifically, the positive electrode sheet comprising a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector, the positive electrode material layer comprising the aforementioned olivine structure positive electrode material. This positive electrode sheet possesses all the advantages of the aforementioned olivine structure positive electrode material, which will not be elaborated upon here.

[0082] In some embodiments, the positive electrode material layer includes the aforementioned olivine structure positive electrode material and auxiliary materials, wherein the olivine structure positive electrode material is the source of battery capacity; the auxiliary materials include positive electrode conductive agents, positive electrode binders, etc., thereby helping to obtain a positive electrode material layer with excellent conductivity.

[0083] In some embodiments, the positive electrode conductive agent includes at least one of Super P and CNT; the positive electrode binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyvinylidene fluoride-hexafluoropropylene, polytetrafluoroethylene, and polyimide. The above-mentioned positive electrode conductive agent and positive electrode binder can be selected according to actual needs.

[0084] In some embodiments, an exemplary method for preparing the positive electrode sheet is as follows: olivine-structured positive electrode material, acetylene black, and polyvinylidene fluoride (PVDF) are thoroughly mixed with an appropriate amount of N-methylpyrrolidone (NMP) at a mass ratio of 95:3:2 to form a uniform slurry. This slurry is coated onto aluminum foil and dried at 120°C for 12 hours. The slurry is then pressed into a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm using a pressure of 100 MPa. The loading of the positive electrode material is 15 mg / cm³. 2 .

[0085] In a fourth aspect of this application, a battery is proposed that includes the aforementioned positive electrode. Thus, this battery possesses all the advantages of the aforementioned positive electrode, which will not be elaborated further here.

[0086] In some embodiments, the battery can be an all-solid-state battery, including the above-mentioned positive electrode, negative electrode and electrolyte material disposed between the positive and negative electrodes. During the charging and discharging process of the battery, active ions are inserted and extracted back and forth between the positive and negative electrodes. The electrolyte material between the positive and negative electrodes mainly plays the role of allowing active ions to pass through.

[0087] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode material layer may include a negative electrode material, a thickener, a conductive agent, and a binder.

[0088] Specifically, the negative electrode current collector can be a metal foil, for example, copper foil. The negative electrode material can include carbon-based materials, silicon-based materials, tin-based materials, etc. The binder in the negative electrode material layer can include, but is not limited to, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethyl methacrylate (PMAA), and carboxymethyl chitosan (CMCS). The conductive agent in the negative electrode material layer can include, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0089] In some embodiments, the separator may be a separator known in the art that can be used in lithium-ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, etc.

[0090] In a fifth aspect of this application, an electrical device is proposed, comprising the aforementioned battery. Therefore, this electrical device possesses high discharge specific capacity, rate performance, and cycle performance.

[0091] In some embodiments, the specific type of electrical device is not particularly limited and can be any device that uses the aforementioned battery as a power source or energy storage unit. For example, electrical devices include, but are not limited to, electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), mobile terminals (e.g., mobile phones, laptops, game consoles, wearable devices, etc.), drones, aerospace equipment, satellites, ships, energy storage systems, and so on.

[0092] It is understood that, in addition to the battery mentioned above, the electrical device also includes other necessary structures and components, all of which can be made with reference to conventional technologies. For example, an electric vehicle may include a body, chassis, tires, navigation system, radar system, steering system, braking system, lubrication system, cooling system, driving system, etc., which will not be described in detail here.

[0093] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.

[0094] Example 1 S1: Preparation of the first lithium iron phosphate particle precursor: Lithium carbonate, iron phosphate, and phosphoric acid were weighed and mixed in a Li:Fe:P molar ratio of 1.03:1:1.01. Glucose and PEG were used as the first carbon source, and TiO2 was used as the dopant. The total mass ratio of lithium carbonate, iron phosphate, and phosphoric acid to the first carbon source was 3:1, and the Ti content in the added dopant was 5000ppm. The above raw materials were dispersed in deionized water to obtain a slurry with a solid content of 40%. The slurry was then subjected to ultrasonic dispersion and ball milling. The ultrasonic dispersion power was 400W for 25min, and the ball milling speed was 500r / min for 1h. Subsequently, spray drying was performed (inlet air temperature 250℃, outlet air temperature 100℃). Preparation of the second lithium iron phosphate particle precursor: Lithium carbonate, iron phosphate, and phosphoric acid were weighed and mixed in a Li:Fe:P molar ratio of 1.03:1:1.01. Sucrose and PVA were used as the second carbon source, and TiO2 and V2O5 were used as dopants. The total mass ratio of lithium carbonate, iron phosphate, and phosphoric acid to the second carbon source was 3:1, and the Ti and V content in the added dopants was 5000 ppm. The above raw materials were dispersed in a solvent (a mixed solvent of deionized water and ethanol in a volume ratio of 2:1) to obtain a slurry with a solid content of 40%. The slurry was then subjected to ultrasonic dispersion and ball milling. The ultrasonic dispersion power was 400 W for 25 min, and the ball milling speed was 500 r / min for 1 h. Subsequently, spray drying was performed (inlet air temperature 250℃, outlet air temperature 100℃).

[0095] S2: The first lithium iron phosphate particle precursor was placed in a microwave sintering furnace. First, under an inert gas atmosphere (argon to nitrogen volume ratio 1:1), the temperature was increased to 400℃ at a rate of 5℃ / min and held for 2 hours. Then, the temperature was increased to 780℃ and held for 8 hours. After natural cooling to room temperature, the first lithium iron phosphate particles, Rp, were obtained. 50 It is 1.82 μm; The second lithium iron phosphate particle precursor was heated to 360°C at a rate of 8°C / min and held for 1 hour, then heated to 755°C and held for 8 hours. After natural cooling to room temperature, the second lithium iron phosphate particles were obtained. Rp 50 It is 0.4μm.

[0096] S3: Mix the first lithium iron phosphate particles and the second lithium iron phosphate particles at a mass ratio of 1:1, and add a composite grinding aid (polyacrylate to nano silica mass ratio of 1:1). The mass of the composite grinding aid is 1 wt% of the total mass of the mixture (i.e., the total mass of the first lithium iron phosphate particles, the second lithium iron phosphate particles, and the composite grinding aid). Disperse the mixture in anhydrous ethanol and use ultrasonic dispersion (power 400W, time 50min) to ensure uniform dispersion. Then, perform vacuum freeze drying (temperature -40℃, vacuum degree 3Pa, time 8h), followed by a third sintering at 760℃ for 9h. After natural cooling to room temperature, finally dry pulverize to D. 50 The diameter is approximately 1.5 μm, yielding the target product (olivine structure cathode material).

[0097] Example 2 Same as Example 1, the main difference is that the sintering time for one stage is 2 hours, and other parameters are shown in Tables 1 to 3.

[0098] Example 3 Same as Example 1, the main difference is that the sintering time for one stage is 3 hours, and other parameters are shown in Tables 1 to 3.

[0099] Example 4 Same as Example 1, the main difference is that the temperature of the two-stage sintering is 750℃ and the temperature of the four-stage sintering is 815℃. Other parameters are shown in Tables 1 to 3.

[0100] Example 5 Same as Example 1, the main difference is that the dopant V2O5 is replaced with MgO, and other parameters are shown in Tables 1 to 3.

[0101] Example 6 Same as Example 1, the main difference is that the dopant V2O5 is replaced with CaO, and other parameters are shown in Tables 1 to 3.

[0102] Example 7 Same as Example 1, the main difference is that only TiO2 is used as the dopant, and other parameters are shown in Tables 1 to 3.

[0103] Example 8 Same as Example 1, the main difference is that the temperature of the two-stage sintering is 720℃, and other parameters are shown in Tables 1 to 3.

[0104] Example 9 Similar to Example 1, the main differences are: the temperature of the two-stage sintering is 830°C, and the temperature of the four-stage sintering is 820°C, the time of the four-stage sintering is 12h, and the iron source used in the preparation of the first lithium iron phosphate particle precursor and the second lithium iron phosphate particle precursor is iron powder, the first carbon source is PAA and citric acid, the second carbon source is glucose and sucrose, and other parameters are shown in Tables 1 to 3.

[0105] Example 10 Similar to Example 1, the main differences are: the sintering time for the first stage is 1 hour, the sintering time for the second stage is 6 hours, the sintering time for the third stage is 1.5 hours, and the sintering temperature for the fourth stage is 780°C, with a sintering time of 9 hours. Other parameters are shown in Tables 1 to 3.

[0106] Example 11 Same as Example 1, the main differences are: the sintering time for the first stage is 1.9h, the sintering time for the second stage is 7h, the sintering time for the third stage is 2.8h, the sintering temperature for the third stage is 400℃, the sintering temperature for the fourth stage is 820℃, the sintering time for the fourth stage is 12h, and other parameters are shown in Tables 1 to 3.

[0107] Example 12 Similar to Example 1, the main difference is that the sintering temperature for the two stages is 710°C, the sintering temperature for the three stages is 350°C, and the sintering temperature for the four stages is 795°C. Other parameters are shown in Tables 1 to 3.

[0108] Comparative Example 1 Similar to Example 1, the main difference is that the preparation of the first lithium iron phosphate particles is not carried out, that is, the second lithium iron phosphate particles obtained are the target particles, and other parameters are shown in Tables 1 to 3.

[0109] Comparative Example 2 Same as Example 1, the main difference is that there is no preparation of the second lithium iron phosphate particles, that is, the first lithium iron phosphate particles obtained are the target particles, and other parameters are shown in Tables 1 to 3.

[0110] Test methods The cathode materials prepared using the above examples and comparative examples were used to prepare cathode sheets, which were then assembled into batteries for electrochemical performance testing.

[0111] The preparation method of the positive electrode sheet is as follows: The lithium iron phosphate positive electrode material, conductive agent Super P, and polyvinylidene fluoride (PVDF) prepared above are thoroughly mixed with an appropriate amount of N-methylpyrrolidone (NMP) at a mass ratio of 96.5:1.5:2 to form a uniform slurry. The slurry is coated on aluminum foil and dried at 120℃ for 12 h. The compaction density of the positive electrode sheet is 2.5 g / cm³. 3 It was then stamped into a positive electrode sheet with a diameter of 12 mm.

[0112] The negative electrode sheet is prepared as follows: silicon carbon, conductive agent Super P, binder CMC, and binder SBR are thoroughly mixed with an appropriate amount of pure water at a mass ratio of 96.3:0.5:1.2:2.0 to form a negative electrode slurry. This slurry is then uniformly coated onto copper foil and dried. The negative electrode sheet is then rolled to achieve a compaction density of 1.55 g / cm³. 3Then, a negative electrode sheet with a diameter of 15mm was cut out using a punching machine.

[0113] Battery fabrication method: In a glove box filled with argon gas and containing water and oxygen content both less than 5 ppm, the positive electrode, separator, negative electrode, and electrolyte were assembled into an R2025 coin cell and then left to stand for 6 hours. The negative electrode used was a lithium metal sheet with a diameter of 15.6 mm and a thickness of 0.45 mm; the separator used was a 25 μm polypropylene microporous membrane (Celgard 2325); and the electrolyte used was a 1 mol / L mixture of equal parts LiPF6, ethylene carbonate (EC), and diethyl carbonate (DEC).

[0114] Test method for 1C discharge capacity: The test conditions for 1C discharge capacity are as follows: under the conditions of 25℃ and voltage range of 2.5V~4.2V, the charging constant voltage cutoff current is 0.05C, 0.1C charge and discharge for 2 cycles, 0.2C-0.33C-0.5C-1C-2C-5C for 1 cycle each, and evaluate the 1C and 5C discharge capacity of the material.

[0115] Test method for 5C rate retention rate: Rate retention rate = 5C discharge capacity / 0.1C first-cycle discharge capacity × 100%.

[0116] Test method for -20℃ low-temperature retention rate: At 25℃, the battery is charged at a constant current of 0.33C to 4.2V, and then charged at a constant voltage of 4.2V until the current drops to 0.05C. The fully charged battery is then transferred to a low-temperature test chamber set at -20±2℃ and left to stand for 2-4 hours to ensure the internal temperature of the battery reaches -20±2℃. Subsequently, at -20℃, the battery is discharged at a constant current of 0.33C to 2.5V, thus obtaining the discharge capacity at -20℃ at 0.33C. -20℃ low-temperature retention rate = (Discharge capacity at -20℃ at 0.33C / Discharge capacity at 25℃ at 0.33C) × 100%.

[0117] Test method for 100-cycle retention rate: After 5 weeks of 0.1C charge-discharge at 45℃, perform 100 cycles of 1C charge-discharge, with a voltage range of 2.5V~3.65V and a constant voltage cutoff current of 0.05C to evaluate the cycle retention rate of the material.

[0118] Test Results The SEM images of the first and second lithium iron phosphate particles prepared in Example 1 are shown below. Figure 1 and Figure 2 The SEM images of the final target product are shown below. Figure 3 It can be seen that the target product has a gradation of large and small particles.

[0119] The electrochemical performance of the batteries prepared in the examples and comparative examples is shown in Table 5.

[0120]

[0121] Conclusion: Based on the data from Examples 1-12 and Comparative Examples 1-2, it can be seen that the relative surface area increment coefficient F of the olivine structure cathode material prepared in this application is within a limited range, its compaction density is high, and the electrochemical performance (discharge capacity, rate retention, low temperature retention, and cycle retention, etc.) of the assembled battery is relatively superior.

[0122] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0123] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0124] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection, an electrical connection, or a connection that allows communication between them; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise explicitly limited. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.

[0125] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0126] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0127] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A cathode material with an olivine structure, characterized in that, The olivine-structured cathode material includes lithium iron phosphate cathode material particles, which comprise a carbon coating layer and a core. The core has the chemical formula Li. a Fe b M c (PO4) d M is selected from at least one of Mn, V, Co, Sr, Ni, La, Ta, Al, Cr, Zr, Ti, Mg, Ca, Nb, Sn, Sb, Mo, Si, and Na, where 0.99≤a≤1.09, 0.7≤b≤1, 0≤c≤0.3, and 0.9≤d≤1.

09. The relative surface area increment coefficient F of the lithium iron phosphate cathode material satisfies: 0.6 ≤ F ≤ 1.8, where F = (SB - Sc) / Sc, and Sc represents the theoretical specific surface area of ​​the olivine structure cathode material in m². 2 / g, SB represents the actual measured specific surface area of ​​the olivine-structured cathode material, in m². 2 / g.

2. The olivine-structured cathode material according to claim 1, characterized in that, 0.7≤F≤1.7。 3. The olivine-structured cathode material according to claim 1, characterized in that, At least one of the following conditions must be met: The Sc of the olivine-structured cathode material is 4.0m. 2 / g~9.0m 2 / g; The SB of the olivine-structured cathode material is 9.0m. 2 / g~15.0m 2 / g.

4. The olivine-structured cathode material according to any one of claims 1 to 3, characterized in that, The theoretical specific surface area of ​​the olivine-structured cathode material is Sc = 6 / (ρ × D). A ), where ρ is 3.6 g / cm³ 3 , representing the true density of the olivine-structured cathode material, D A The value represents the average particle size of the lithium iron phosphate cathode material particles, expressed in μm.

5. The olivine-structured cathode material according to claim 4, characterized in that, The particle size distribution curve of the olivine structure cathode material includes two characteristic peaks. The peak position of the first characteristic peak is 0.3 μm to 0.7 μm, and the peak position volume percentage of the first characteristic peak is Pv1. The peak position of the second characteristic peak is 1.0 μm to 2.5 μm, and the peak position volume percentage of the second characteristic peak is Pv2. The peak intensity ratio I of the volume distribution of the olivine structure cathode material satisfies: 0.7 ≤ I = Pv1 / Pv2 ≤ 1, preferably 0.75 ≤ I = Pv1 / Pv2 ≤ 0.

96.

6. The olivine-structured cathode material according to claim 5, characterized in that, At least one of the following conditions must be met: Pv1 was 4%~6%; Pv2 is 5%~7%.

7. The olivine-structured cathode material according to any one of claims 1 to 6, characterized in that, At least one of the following conditions must be met: The D of the olivine structure cathode material 50 The micrometer size is 0.8 μm to 2.0 μm, preferably 1.0 μm to 1.8 μm; Based on the total mass of the olivine-structured cathode material, the carbon content is 1.0 wt%~2.0 wt%; The compaction density of the olivine-structured cathode material is 2.60 g / cm³. 3 ~2.90g / cm 3 .

8. A method for preparing an olivine-structured cathode material as described in any one of claims 1 to 7, characterized in that, include: First lithium iron phosphate particle precursor and second lithium iron phosphate particle precursor were prepared respectively. The first lithium iron phosphate particle precursor is subjected to a first sintering to obtain the first lithium iron phosphate particles, and the second lithium iron phosphate precursor is subjected to a second sintering to obtain the second lithium iron phosphate particles. The first lithium iron phosphate particles, the second lithium iron phosphate particles, the grinding aid and the solvent are mixed, dried, pulverized and sintered in sequence to obtain an olivine structure cathode material. Among them, the R of the first lithium iron phosphate particle p50 The R of the second lithium iron phosphate particles is 0.4μm~1μm. p50 The range is 1.43μm to 3.33μm.

9. The preparation method according to claim 8, characterized in that, At least one of the following conditions must be met: The preparation method of the first lithium iron phosphate particle precursor includes: mixing a lithium source, an iron source, a phosphorus source, an optional dopant, a first carbon source according to a target chemical ratio and a solvent, and spray drying to obtain the first lithium iron phosphate particle precursor, wherein the first carbon source includes at least one of glucose, sucrose, PVP, oxalic acid, water-soluble phenolic resin, PAA, starch, ascorbic acid, citric acid, lignin, PEG, and PVA. The preparation method of the second lithium iron phosphate particle precursor includes: mixing a lithium source, an iron source, a phosphorus source, an optional dopant, a second carbon source according to a target chemical ratio and a solvent, and spray drying to obtain the second lithium iron phosphate particle precursor. The second carbon source includes at least one of glucose, sucrose, PVP, oxalic acid, water-soluble phenolic resin, PAA, ascorbic acid, citric acid, starch, asphalt, PEG, and PVA.

10. The preparation method according to claim 9, characterized in that, At least one of the following conditions must be met: The iron source includes at least one of ferric carbonate, ferrous oxide, ferric oxide, iron powder, ferric oxide, ferrous oxalate, and ferric phosphate. The lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, lithium oxide, lithium dihydrogen phosphate, and lithium phosphate. The phosphorus source includes at least one of sodium phosphate, potassium phosphate, phosphoric acid, and monoammonium phosphate.

11. The preparation method according to claim 8, characterized in that, The first sintering includes sequentially performing a first-stage sintering and a second-stage sintering, and the second sintering includes sequentially performing a third-stage sintering and a fourth-stage sintering, and satisfies at least one of the following conditions: The sintering rate of the first section is 5℃ / min~8℃ / min; The sintering temperature of the first section is 400℃~450℃; The sintering time for the first stage is 2 to 3 hours. The sintering rate of the two stages is 5℃ / min~8℃ / min; The temperature for the two-stage sintering is 750℃~830℃; The sintering time for the two stages is 6 hours to 15 hours. The sintering rate of the three sections is 5℃ / min~8℃ / min; The sintering temperature for the three stages is 350℃~400℃; The sintering time for the three stages is 1 hour to 2 hours; The sintering rate of the four sections is 5℃ / min~8℃ / min; The sintering temperature for the four sections is 680℃~780℃; The sintering time for the four sections is 4h~12h; The temperature of the third sintering is 720℃~800℃; The third sintering time is 5h~14h.

12. The preparation method according to claim 9, characterized in that, At least one of the following conditions must be met: The mass ratio of the first lithium iron phosphate particle to the second lithium iron phosphate particle is (1:5) to (2:1); Based on the total mass of the first lithium iron phosphate particles, the second lithium iron phosphate particles, and the grinding aid, the mass percentage of the grinding aid is 0.1wt%~2wt%. The grinding aid includes inorganic grinding aid and organic grinding aid, and the mass ratio of the inorganic grinding aid to the organic grinding aid is (1~5):(1~5). The dopant includes at least one of the following: oxide, hydroxide, sulfate, carbonate, phosphate, fluoride, and chloride of M.

13. The preparation method according to claim 8, characterized in that, The drying is vacuum freeze-drying, and the vacuum freeze-drying satisfies at least one of the following conditions: The temperature for vacuum freeze drying is -40℃ to -50℃; The vacuum degree of the vacuum freeze-drying is 1 Pa to 5 Pa; The vacuum freeze-drying time is 8h~12h.

14. The preparation method according to claim 12, characterized in that, At least one of the following conditions must be met: The inorganic grinding aid includes at least one of metal oxides and phosphates; The organic grinding aid includes at least one of polyacrylates, alcohols, and fatty acids.

15. A positive electrode plate, characterized in that, This includes the olivine-structured cathode material according to any one of claims 1 to 7, or the olivine-structured cathode material obtained by the preparation method according to any one of claims 8 to 14.

16. A battery, characterized in that, Includes the positive electrode sheet as described in claim 15.

17. An electrical device, characterized in that, Includes the battery as described in claim 16.